Tổng hợp và nghiên cứu một số N-aryliđen[5-(menthoximetyl)-4-phenyl-1,2,4-triazol- 3-ylsunfanyl]axetohiđrazit - Sơn, Trần Quốc; Liên, Hoàng Thị; Công, Nguyễn Tiến (Vietnam Journal of Chemistry, 2014)
Starting from menthol, 14 compounds containing menthane skeleton have been synthesized; 12 of them are 1,2,4-triazole derivatives. Their structure have been determined by UV, IR, 1D NMR, 2D NMR and MS spectral data. Some synthesized compounds were tested for bactericidal and fungicidal activities